Structural correlates of moral emotions in patients with behavioral variant frontotemporal dementia. (31st December 2021) - Chonchol, Andrea Slachevsky; Trujillo, Catalina; Forno, Gonzalo; Bleier, Cristina; Lillo, Patricia; de Souza, Leonardo Cruz; Baez, Sandra
Abstract: Background: Social cognition impairments have been extensively described in patients with behavioral variant frontotemporal dementia (bvFTD). Moral emotions have recently emerged as a potentially sensitive domain to characterize and discriminate bvFTD patients from other types of dementia. Here, we examined the usefulness of moral emotions measures to characterize and discriminate bvFTD from Alzheimer's disease (AD) patients, and their structural brain correlates in both groups. Method: In this multicenter (Chile‐Colombia) study, 31 bvFTD, 30 AD patients, and 37 healthy controls –matched by age, sex, and educational level– completed an adapted version of the Moral Sentiments Association Task (MSAT) consisting of 29 text‐based scenarios evoking moral (guilt, pity, embarrassment, and indignation) and basic (fear and disgust) emotions. After reading each scenario, participants selected the emotion they would feel in that situation and rated their elicited intensity and disturbance levels. General cognitive (MoCA/ACE‐III) and executive (IFS) measures were also included. Additionally, we performed VBM analysis in a subsample (15 bvFTD, 20 AD, 17 controls) to study the association between grey matter volumes and moral emotions processing Result: After controlling for cognitive and executive skills, bvFTD patients exhibited lower accuracy on identifying moral emotions –pity, embarrassment, and indignation– than AD patients, despite null differences in basic emotions. Subsequent discriminant analysis revealed that this differential pattern classified patient groups more accurately (74%: 65% bvFTD and 83% AD) than individual cognitive (59%) and executive (51%) measures. Crucially, between‐group classification substantially improved when combining the three measures mentioned above (79%: 68% bvFTD, 90% AD). In both groups, pity, embarrassment, and indignation identification correlated with reduced grey matter volumes in regions subserving social cognition and emotion processing, including the Rolandic operculum, the inferior and middle temporal gyri, and the postcentral gyrus (exclusive to bvFTD). Conclusion: These results suggest that bvFTD patients exhibit moral emotion impairments as compared with AD patients. Particularly, pity, embarrassment, and indignation emerged as useful measures to patients' classification. Such findings contribute to a better understanding of the structural correlates of moral emotional deficits in bvFTD patients while highlighting the potential benefits of integrating this domain into the standard cognitive and executive assessment for a more accurate differential diagnosis.